Development of an online exam system for students of SMK Negeri 7 Samarinda - Noor Alam Hadiwijaya; Damar Nurcahyono; Farindika Metandi; Abdul Najib (Community Empowerment, 2022)
An exam is a type of examination or evaluation used to assess a person's abilities. Meanwhile, developing an online exam system in schools can help with the correction process. The waterfall method was utilized to design the system. The waterfall approach is used to carry out the procedure in a sequential manner. The system can be accessible by three types of users: administrators, teachers, and students. The implementation of an online exam system in schools has shown to aid teachers in the correction process, allowing grades to be acquired immediately following the exam.